Fenomena Alih Kode Dan Campur Kode Dalam Angkutan Umum (ELF) Jurusan Sindang Terminal_Harjamukti Cirebon - Fauziyah, Ayu; Itaristanti, Itaristanti; Mulyaningsih, Indrya (SEBASA Jurnal Pendidikan Bahasa dan Sastra, 2019)
His study aims to describe the form of transfer and code mixing in public transport (elf) Sindang-Terminal Harjamukti Cirebon Department. The qualitative descriptive approach used in this study is the elaboration of data in the analysis. The results obtained from this study are a form of code switching and code mixing in public transportation (elf) Sindang-Terminal Harjamukti Cirebon Department and its causes. The form of code switching includes internal code switching which includes code switching between languages and code switching between languages and external code switching. The cause of the occurrence of code switching is that the interlocutor has a different language background than the speaker, the speaker has a desire to respect his interlocutor who is older than him, and the limited use of the code. The form of code mixing includes code mixing in the repetition of words and kalusa, mixing code out at the level of phrases and idioms, and mixing mixed codes of baster forms. The reason for code interfering occurs when speakers want to be able to use more popular terms, speakers have a specific purpose and purpose in the conversation, to be just prestigious, and to adjust language use to the topic of conversation.Keywords : the form of code switching; the factors that cause code switching; the form of code mixing; the causes of code interfering.